Pancasila dan Penegakan Hukum terhadap Tindak Pidana Korupsi di Indonesia: Pancasila and Law Enforcement Against Corruption in Indonesia - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Galang Andra Ristian; Nur Hanafi Muafa; Albryan Wahyu Putra Sejati; Erlangga Adiarta (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
Pancasila as the foundation of the state and the ideology of the Indonesian nation has a fundamental role in law enforcement, including in eradicating corruption. As an extraordinary crime, corruption not only harms state finances but also erodes moral values and public trust in state institutions. The principles of Pancasila, such as social justice, just and civilized humanity, and the supremacy of law, provide a normative basis for efforts to eradicate corruption. Law enforcement against corruption in Indonesia has been attempted through institutions such as the Corruption Eradication Commission (KPK), the Prosecutor’s Office, and the Police, as well as through legal instruments such as Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 concerning the Eradication of Corruption. However, challenges such as political intervention, weak integrity of law enforcers, and the complexity of corruption cases still hamper the effectiveness of law enforcement. To strengthen the eradication of corruption, it is necessary to strengthen the anti-corruption culture based on Pancasila values, institutional reform, and a joint commitment from all elements of the nation. By implementing Pancasila as an ethical and practical guideline, it is hoped that a just legal system and a more responsible society will be created in maintaining the integrity of the nation. This abstract underlines the importance of collaboration between the values of Pancasila and the supremacy of law to combat corruption in Indonesia.